ANTIBACTERIAL ACTIVITY OF TRIFLUOPERAZINE; IN VITRO SUSCEPTIBILITY OF MRSA STAPHYLOCOCCUS AUREUS, PSEUDOMONAS AERUGINOSA AND E. COLI, AND IN VIVO EVALUATION AGAINST METHICILLIN RESISTANT STAPHYLOCOCCUS AUREUS IN SURGICAL WOUND INFECTION MODEL - S. Ashok1; M. Ejaz; A. Manzoor; M. F. Qadir2; S. Nazir (Journal of Animal and Plant Sciences, 2021)
Management of surgical site infections (SSI) becomes very difficult due to Bacterial resistance. Current study was designed to determine in vitro susceptibility and minimum inhibitory concentration of trifluoperazine against MRSA, Staphylococcus aureus, Pseudomonas aeruginosa and E. coli, and determination of in vivo antibacterial activity of trifluoperazine in induced surgical site infections by MRSA. In vitro antibacterial activity of trifluoperazine was determined by disc diffusion susceptibility testing while determination of MIC by agar dilution technique. In vivo antibacterial activity was observed by microbiological assessment of tissue harvested from the experimentally infected wound site and number of colony forming units per gram (cfu/gm) of tissue. The zones of growth inhibition of trifluoperazine were determined against MRSA, E. coli and Pseudomonas aeruginosa. At a disc potency of 25 µg no zone of inhibition was produced against any isolate. 50 µg produced 13 mm and 16 mm zone of inhibition against MRSA and Pseudomonas aeruginosa respectively. Whereas, No zone against E. coli was observed at this concentration but, 12mm, 15mm and 18mm zones of inhibition were produced by 100 µg, 150 µg, and 200 µg per disc concentration of trifluoperazine respectively. The colony forming units/gram observed in trifluoperazine treated wounds were 2.93±0.02 x 10⁶ while in case of normal saline treated wounds the value was 6.68±0.07 x 10⁶. Results revealed the efficacy of trifluoperazine as a potentially therapeutic agent in the treatment of wound infection beds especially against MRSA.
Keywords: Trifluoperazine; Staphylococcus; Methicillin; Antibacterial; Wound Infection